Aplicación móvil para la lectura pictográfica en el proceso de enseñanza aprendizaje en los niños y niñas del primer año de Educación Básica en la Unidad Educativa Victoria Vásconez Cuvi - Simón Bolívar - Elvira Ortega de la ciudad de Latacunga. - Landeta Tapia, Mayk Estefano (2020)
Mobile application of video game type as support tool for Victoria Vásconez Cuvi Educational Unit teachers - Simón Bolívar - Elvira Ortega of Latacunga city with pictographic content of the characters Mama Negra parade which is a festivity from Latacunga, for its development there were used bibliographic, field and descriptive research techniques and instruments such as survey and checklist used for data collection and analysis; In addition Cronbach alpha coefficient was applied to verify the hypothesis through statistical software (SPSS). The development model is the Iterative - Incremental that allowed to divide the project into four fully functional and deliverable iterations, for each analysis were designing, coding and testing phases were executed. As App results it was shown that children entertain themselves and at the same time learn through pictographic reading about the parade, they also manage to solve a test of recognition of “Mama Negra” characters celebration through the Evaluation module included at the App. These results allow to conclude that the determined objectives for this work have been fully met.